1986
DOI: 10.1111/j.1600-0714.1986.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of keratin in experimental carcinoma of the mouse submandibular gland

Abstract: An immunohistochemical survey of the distribution of keratin was studied in chemically induced carcinomas of the submandibular glands of mice. Initial signs of premalignant changes were degranulation of granular convoluted tubule cells and deposition of keratin protein in small limited areas of the degranulated cells. There was a gradual increase in the area showing keratin staining in altered tubule cells. Duct‐like and cystic structures stained intensely for keratin, as did squamous metaplastic epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Keratin prtiteins appeared in these degranulated GCT cells, while salivary growth factors like EGF and NGF were reduced or disappeared from the cells (4). A similar correlation between reduced EGF reactitm and increased keratin staining has been found in the early stage of experimentally-indueed eareintimas in mtiuse SMGs (13,14). The GCT eells are thtiught to be the eells whieh transform into eareinomas (15,16); furthermore, sueh altered GCT cells stained ftir keratin.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Keratin prtiteins appeared in these degranulated GCT cells, while salivary growth factors like EGF and NGF were reduced or disappeared from the cells (4). A similar correlation between reduced EGF reactitm and increased keratin staining has been found in the early stage of experimentally-indueed eareintimas in mtiuse SMGs (13,14). The GCT eells are thtiught to be the eells whieh transform into eareinomas (15,16); furthermore, sueh altered GCT cells stained ftir keratin.…”
Section: Discussionsupporting
confidence: 70%
“…The GCT cells of SMGs of mice and rats are characterized by the marked presence of salivary gland growth factors such as epidermal growth factor (EFCJ) and nerve growth factor (NGF) (5)(6)(7)(8)(9), and these factors are greatly reduced following duct ligation; the reduction is proportional to the degree of degranulation of the GCT cells (4). Studies on the immunohistochemical detection of keratin proteins in both minor and major salivary glands have revealed that ductal epithelia of abundance salivary glands contain and abundance of keratin (10)(11)(12)(13). TTie present immunohistochemical study was undertaken to compare the keratin distribution in SMGs following duct-ligation, to the localization of EGF and NGF under the same conditions as previously reported (4).…”
mentioning
confidence: 99%
“…Hyperplasia of striated duct basal cells seems to be involved in the pathogenesis of some membranous basal cell adenomas (Yu et al, 1998). Premalignant changes, including degranulation and squamous metaplasia of granular convoluted ducts, precede the development of chemical carcinogen-induced carcinoma of the mouse submandibular gland (Takai et al, 1986). However, before the availability of transgenic mouse models there was no direct evidence implicating specific cell types in the genesis of salivary tumors.…”
Section: Dardick Et Almentioning
confidence: 99%
“…Although all ductal segments are potential sites for developing experimental cancer, acinar cells do not appear to be involved in the metaplastic process (Sumitomo et al, 1996;Takai et al, 1986). The granular convoluted tubule cells are the targets in chemical submandibular gland carcinogenesis (Takai et al, 1986).…”
Section: Experimental Aspectsmentioning
confidence: 99%
“…The granular convoluted tubule cells are the targets in chemical submandibular gland carcinogenesis (Takai et al, 1986).…”
Section: Experimental Aspectsmentioning
confidence: 99%